Effective and efficient bunker operations, logistics, procurement, developments in the maritime industry (Part 3) Efficient bunker hedging in the perspective of tramp ship operators - Wong, Jyun Yao (2016)
Bunkers made up the bulk of the voyage costs. Unlike port costs, which also constitute a major portion to the voyage costs, bunker prices are always fluctuating. Ship operators are therefore exposed to bunker price risk. This risk can be minimised through bunker hedging. Bunker hedging has not been widely investigated into, especially in the context of tramp operators compared to liner operators. Using bunker hedging in the perspective of tramp shipping companies as the base, the focus of this report is to first analyse the various hedging instruments available based on their hedging objectives and working mechanisms, followed by a brief evaluation of whether tramp operators should hedge bunkers using qualitative approach. Lastly, the concept of bunker alliance in bunker hedging for tramp ship operators, an idea that arise from the economies of scale derived from liner alliances, will be explored. It has been identified that fixed price agreements and swaps are the more suitable hedging instruments as they achieve greater cost control and cash flow certainty and are simple to implement. Call options can serve as supportive hedging instrument as a form of insurance against bunker price hikes. Bunkers are inherently hedged with the presence of BAF clause in COAs. For spot voyages, effective and efficient bunker hedging is highly dependent on the accuracy of the forecast. The irony of hedging is that if you succeed, you are better off but if you fail, you are worse off. Despite this, it seemed that larger tramp operators will benefit more from bunker hedging as the costs and savings are better justified due to larger hedged volumes and the availability of more resources. The bunker alliance concept is theoretically feasible but practically unworkable. There lies a possibility of the ‘bunker alliance’ initiated by the bunker traders and suppliers through the establishment of a new market for fixed price agreements, similar to the ‘Groupon’ concept with the help of technology. However, its feasibility has to be further studied.